A New Proof of Concept in Bacterial Reduction: Antimicrobial Action of Violet-Blue Light (405 nm) in Ex Vivo Stored Plasma. (28th September 2016) - Maclean, Michelle; Anderson, John G.; MacGregor, Scott J.; White, Tracy; Atreya, Chintamani D.
Abstract : Bacterial contamination of injectable stored biological fluids such as blood plasma and platelet concentrates preserved in plasma at room temperature is a major health risk. Current pathogen reduction technologies (PRT) rely on the use of chemicals and/or ultraviolet light, which affects product quality and can be associated with adverse events in recipients. 405 nm violet-blue light is antibacterial without the use of photosensitizers and can be applied at levels safe for human exposure, making it of potential interest for decontamination of biological fluids such as plasma. As a pilot study to test whether 405 nm light is capable of inactivating bacteria in biological fluids, rabbit plasma and human plasma were seeded with bacteria and treated with a 405 nm light emitting diode (LED) exposure system (patent pending). Inactivation was achieved in all tested samples, ranging from low volumes to prebagged plasma. 99.9% reduction of low density bacterial populations (≤10 3 CFU mL −1 ), selected to represent typical "natural" contamination levels, was achieved using doses of 144 Jcm −2 . The penetrability of 405 nm light, permitting decontamination of prebagged plasma, and the nonrequirement for photosensitizing agents provide a new proof of concept in bacterial reduction in biological fluids, especially injectable fluids relevant to transfusion medicine.